Characterizing Circular Supply Chain Practices in Industry 5.0 With Respect to Sustainable Manufacturing Operations - Sami, Abdul; Manzoor, Umair; Irfan, Asmara; Sarwar, Farhan (Journal of Management and Research, 2023)
The current research investigated the significance of circular supply chain practices in Industry 5.0 with respect to their sustainable manufacturing operations. Through a comprehensive review of the literature, the current study identified key circular supply chain practices and their potential benefits for Industry 5.0. The findings indicated that closed-loop supply chains, sustainable sourcing, product design for circularity, and waste reduction may assist Industry 5.0 firms to achieve their sustainability objectives while enhancing the operational efficiency. Moreover, the study also highlighted the challenges associated with the implementation of circular supply chain practices including the necessity for collaboration among supply chain partners, investment in new technologies and infrastructure, and the development of new skills and capabilities. From a practical and managerial perspective, the implications suggest that firms aiming to adopt circular supply chain practices in Industry 5.0 should prioritize collaboration and coordination, make investments in new technologies and infrastructure, and foster the acquisition of new skills and capabilities. To complement this research, future studies could employ empirical research methods in order to validate the findings and recommendations as well as explore potential barriers to the implementation of circular supply chain practices in Industry 5.0.